2010
DOI: 10.1002/hfm.20224
|View full text |Cite
|
Sign up to set email alerts
|

The effects of force and exertion duration on duty cycle time: Implications for productivity

Abstract: Ergonomics has positive effects on both physical health and productivity, but estimating productivity benefits is difficult at the task design/redesign stage. Rest allowance prediction models are not suitable for repetitive short cycle dynamic tasks and MTM techniques are limited in their suitability for considering ergonomics risk factors such as posture and force. The purpose of this study was to investigate the relationship between force and exertion duration on self selected duty cycle time and discomfort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Finneran and O'Sullivan (2010b) included 20% and 40% grip MVCs in the study of the effects of force and duration of exertion on self-paced duty cycle time in a simulated task. They found a significant difference between these two levels on discomfort and duty cycle time.…”
Section: Treatments and Experiments Designmentioning
confidence: 99%
“…Finneran and O'Sullivan (2010b) included 20% and 40% grip MVCs in the study of the effects of force and duration of exertion on self-paced duty cycle time in a simulated task. They found a significant difference between these two levels on discomfort and duty cycle time.…”
Section: Treatments and Experiments Designmentioning
confidence: 99%
“…A supporting argument for the fatigue hypothesis could be that, during the first chunk of day 2, the participants started at a higher performance level compared to the first chunk of day 1. They may thus have recruited more endurance resources early during the daily session and may have reached their physical exhaustion phase faster on day 2 (Finneran and O'Sullivan, 2010). It is shown that motor learning procedures lead to better results when the practice is done over several days or even weeks (Shea et al, 2000).…”
Section: Online Learningmentioning
confidence: 99%
“…Previously published studies by the current authors involved psychophysical experiments investigating and modelling the relationship between physical risk factors (force, duration of exertion, posture and grip type) and operator performance, with discomfort as a mediator (Finneran andO'Sullivan 2010a and2010b). The current experiment expands on those studies by studying the effects of grip type in conjunction with grip force and wrist posture on duty cycle time (as a measure of on-job productivity or presenteeism) in a simulated task.…”
Section: Introductionmentioning
confidence: 97%
“…Initial cycle time was set at 5 seconds so that DCT would be 40%. Models developed by Finneran and O'Sullivan (2010b) and Abu-ali et al (1996) found that in high force conditions average maximum DCT was approximately 40%.…”
Section: Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation